Becoming a gay caretaker of a religious image (Camarero): Catholic devotion in the Philippines as a gendered social practice - Peter Romerosa; John Francis Antonio (SIMULACRA: JURNAL SOSIOLOGI, 2021)
Pagsasanto or the beliefs and practices associated with the caretaking of religious images is a Catholic devotion brought by the Spanish colonization in the Philippines. The history of pagsasanto illuminates a religious tradition exclusively performed by old-rich women (camareras) and prominent political families. At present, the changing gender roles in pagsasanto through the growing participation of gay caretakers of religious images (camareros) has redefined the practice. This shift prompted the researchers to investigate how gender mediates a devotional practice and how gender is constructed, negotiated, and performed through pagsasanto. Using ethnography, the researchers did participant observation to examine the meanings and practices associated with pagsasanto activities such as decorating the image and its carriage as well as joining the procession. To facilitate further analysis, interviews and focus group discussions were undertaken among four gay informants, highlighting their life histories as image caretakers. Data were categorized through themes and analysed from a critical cultural perspective. The research found that gender mediates pagsasanto and vice versa. The becoming of a gay camarero is rooted in cultural practice and familial Catholic tradition. The changing meanings of pagsasanto arecontingent on gender performativity, market, social media and the growingcommunity networks.